Sequence and biochemical analysis of vaccinia virus A32 protein: Implications for in vitro stability and coiled-coil motif mediated regulation of the DNA-dependent ATPase activity - Uma Ramakrishnan; Tanvi Aggarwal; Kiran Kondabagil (PLoS ONE, 2025)
Nucleocytoplasmic large DNA viruses (NCLDVs) have massive genome and particle sizes compared to other known viruses. NCLDVs, including poxviruses, encode ATPases of the FtsK/HerA superfamily to facilitate genome encapsidation. However, their biochemical and structural characteristics are yet to be discerned. In this study, we demonstrate that the viral ATPases are significantly shorter than their bacterial homologs, representing the minimal ATPase core of the FtsK/HerA superfamily. We analysed the sequence and secondary structural features of the vaccinia virus A32 protein and determined their roles in the protein’s ATPase activity. We sought to purify A32 by various techniques and noted that recombinant A32 expressed in E. coli is highly insoluble and unstable in solution. N-terminal fusion with the thioredoxin solubility tag could alleviate this issue to some extent, but subsequent tag cleavage results in increased susceptibility to precipitation and degradation. We have also predicted a highly conserved coiled-coil motif (CCM) towards the C-terminus of vaccinia virus A32. ATPase activity of A32 is known to increase in the presence of DNA. Comparative analysis of the wildtype protein versus its CCM mutants suggests that this DNA dependence of A32’s ATPase activity is likely regulated by the CCM. We demonstrate that oligomerization of A32, mediated by the CCM, is required for its DNA-binding but is not dependent on ATP- or DNA-binding. Our findings suggest a key role of the CCM, and thus, higher-order structure formation in the regulated ATPase activity of A32, providing new opportunities for further detailed characterization of the poxvirus genome packaging process.